2016
DOI: 10.3233/npm-16915121
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal listeriosis: Uncommon or misdiagnosed?

Abstract: The incidence of perinatal and neonatal Listeriosis is underestimated due undiagnosed stillbirths, misdiagnosis of NL and underreporting of single case reports. Recent outbreaks reinforce the need for better surveillance and targeted health education in certain population groups especially during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Improvements in methods of tracing Listeria infections (Moura et al, 2016;Jackson et al, 2016), increased awareness of listeriosis among clinicians, and the greater number of databases searched in the present study may have contributed to this increase in number of cases; however, it is speculated that the number of cases of listeriosis in mainland China may have been underestimated previously. The serious clinical manifestations and high mortality of listeriosis may have resulted in missed or incorrect diagnoses in past decades, which may also have contributed to an underestimation of the number of patients with listeriosis in the past (Kylat et al, 2016;Zolin et al, 2017). Further research is needed to prove this.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in methods of tracing Listeria infections (Moura et al, 2016;Jackson et al, 2016), increased awareness of listeriosis among clinicians, and the greater number of databases searched in the present study may have contributed to this increase in number of cases; however, it is speculated that the number of cases of listeriosis in mainland China may have been underestimated previously. The serious clinical manifestations and high mortality of listeriosis may have resulted in missed or incorrect diagnoses in past decades, which may also have contributed to an underestimation of the number of patients with listeriosis in the past (Kylat et al, 2016;Zolin et al, 2017). Further research is needed to prove this.…”
Section: Discussionmentioning
confidence: 99%
“…The first prospective clinical study, the Multicentric Observational NAtional Study on LISteriosis and ListeriA (MONALISA), found that the disease burden of listeriosis is higher than previously estimated: particularly, that more than 80% of infected mothers experienced major fetal or neonatal complications, and that the rate of fetal loss was significantly greater at <29 weeks of gestation (Charlier et al, 2017). Underreporting of pregnancy-associated listeriosis is very likely due to undiagnosed asymptomatic illness, unreported/unrecognized early miscarriage, misdiagnosed stillbirths, and difficulty in positively identifying Lm by standard laboratory culture, and Gram stain (Kylat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Positive blood culture for diphtheria or Haemophilus in a septic neonate should alert physicians to possible Listeria infection. Cultures should be carefully examined to ensure that there is no mistake regarding differentiation from other microorganisms 4 . The suspicion of Listeria infection should be reinforced with the laboratory so that specific tests can be performed to differentiate this group of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cephalosporins and chloramphenicol are not active against Listeria and empirical treatment schemes for neonatal meningitis including these antimicrobials do not provide effective coverage 7 . With an appropriate clinical response, ampicillin alone may be continued for 14 days and a course of 21 days is recommended for more severe infections or meningitis treatment 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation